2020
DOI: 10.1038/s41598-020-75298-w
|View full text |Cite|
|
Sign up to set email alerts
|

Experimental and computation assessment of thermomechanical effects during auxetic foam fabrication

Abstract: Auxetic foams continue to interest researchers owing to their unique and enhanced properties. Existing studies attest to the importance of fabrication mechanisms and parameters. However, disparity in thermo-mechanical parameters has left much debate as to which factors dominate fabrication output quality. This paper provides experimental, computational, and statistical insights into the mechanisms that enable auxetic foams to be produced, using key parameters reported within the literature: porosity; heating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Open cell polyurethane foams with two different cell structures were thermo-mechanically fabricated from 32 (z-axis) by 32 (x-axis) by 96 (y-axis) mm samples (PUR30FR, Custom Foams, as used in [35,55,75]). Fabrication conditions and, hence, imparted cell structures were selected based on previous work to give high magnitude NPR in all three orthogonal axes [58,67,76] or just one axis [55,57,62,77]. For the uniform triaxial conversions, compression to 40% engineering strain was imposed with aluminium moulds to modify cell shape in each axis (Figure 1a), giving a volumetric compression ratio (final/original volume) of five.…”
Section: Fabrication: Open Cell Foamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Open cell polyurethane foams with two different cell structures were thermo-mechanically fabricated from 32 (z-axis) by 32 (x-axis) by 96 (y-axis) mm samples (PUR30FR, Custom Foams, as used in [35,55,75]). Fabrication conditions and, hence, imparted cell structures were selected based on previous work to give high magnitude NPR in all three orthogonal axes [58,67,76] or just one axis [55,57,62,77]. For the uniform triaxial conversions, compression to 40% engineering strain was imposed with aluminium moulds to modify cell shape in each axis (Figure 1a), giving a volumetric compression ratio (final/original volume) of five.…”
Section: Fabrication: Open Cell Foamsmentioning
confidence: 99%
“…During such impact tests, a drop mass is decelerated by the energy absorbing material within the product, imparting variable strain rates up to and above 200 s −1 that reduce to 0 s −1 at maximum compression. Despite the wealth of research into auxetic open cell foam, most of the previous work measured Poisson's ratio and Young's modulus quasi-statically (<1 s −1 , [34,54,60,[67][68][69][70]), or at intermediate (<10 s −1 , [52]) strain rates. Poisson's ratios of auxetic open cell foams, between 0 and −0.1, have been measured using marker tracking during impact tests at higher, but variable, strain rates of ~100 s −1 [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…From a synthesis point of view, the alveolar polyurethane foams are the products of a chemical reaction of a polyisocyanate, polyol, and a blowing agent. 21 This class of polymers can lead to flexible foams, rigid or semirigid, according to the composition and chemical structure of the used reagents. 22 The expected filled polyurethane foam within open cells will be physiochemically characterized and evaluated under dynamic tests.…”
Section: Methodsmentioning
confidence: 99%
“…The final conclusions of the DoE showed that the VCR is the most statistically important manufacturing, while no significant statistical correlation could be identified with the temperature, heating times provided and the cooling methodologies. Critchley et al [70] recently provided an updated statistical approach for the optimization of the manufacturing parameters to improve the efficiency of the production. An optimal combination of VCR, porosity and heating time was recommended for a conversion temperature of 200 °C, detailed parameters are also shown in Figure . 10.…”
Section: Parametric Manufacturingmentioning
confidence: 99%